The Influence of NPWP Ownership Obligations, Taxpayer Compliance, Tax Audits and Tax Collection on Tax Receipts at KPP Pratama Jakarta Jatinegara - Sahla Fauziah; Yuppy Triwidatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to understand the influence of the obligation to have a Taxpayer Identification Number (NPWP), taxpayer compliance, tax audits, tax collection in increasing tax revenue at KPP Pratama Jakarta Jatinegara. The population used in this study were taxpayers registered at KPP Pratama Jakarta Jatinegara with a total sample of 94 registered taxpayers. This study uses a quantitative descriptive research method and the sampling method used in this study is by using the Incidental Sampling technique while the data analysis technique used in this study is multiple regression analysis. The results of this study indicate that the obligation to have a Taxpayer Identification Number (NPWP), taxpayer compliance, tax audits, tax collection have a simultaneous and partial effect on tax revenues at KPP Pratama Jakarta Jatinegara.